We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
281
1
avatar+4 

Wanted to check if essay writer solved my problem X(squared) - 6x - 39 = 0 right:

 

x2 - 6x - 39 = 0

D = b2 - 4ac = (-6)2 - 4·1·(-39) = 36 + 156 = 192

x1 = 6 - √1922·1 = 3 - 4√3 ≈ -3.9282032302755088

x2 = 6 + √1922·1 = 3 + 4√3 ≈ 9.928203230275509

 

Is it correct?

 Feb 22, 2018
 #1
avatar+22010 
0

Wanted to check if essay writer solved my problem X(squared) - 6x - 39 = 0 right:

 

It is correct!

 

We proof: \(x_1 = 3-4\sqrt{3}:\)

\(\large{ \begin{array}{|rcll|} \hline x^2-6x-39 &=& 0 \quad & | \quad x_1 = 3 - 4\sqrt{3} \\ (3 - 4\sqrt{3})^2-6(3 - 4\sqrt{3})-39 & \overset{?}{=} & 0 \\ 9 - 24\sqrt{3} + 16\cdot 3 - 18 + 24\sqrt{3} - 39 & \overset{?}{=} & 0 \\ 9 + 16\cdot 3 - 18 - 39 & \overset{?}{=} & 0 \\ 9 + 48 - 18 - 39 & \overset{?}{=} & 0 \\ 57-57 & \overset{?}{=} & 0 \\ 0 & = & 0\ \checkmark \\ \hline \end{array} }\)

 

We proof \(x_2 = 3+4\sqrt{3}:\)

\(\large{ \begin{array}{|rcll|} \hline x^2-6x-39 &=& 0 \quad & | \quad x_2 = 3 + 4\sqrt{3} \\ (3 + 4\sqrt{3})^2-6(3 + 4\sqrt{3})-39 & \overset{?}{=} & 0 \\ 9 + 24\sqrt{3} + 16\cdot 3 - 18 - 24\sqrt{3} - 39 & \overset{?}{=} & 0 \\ 9 + 16\cdot 3 - 18 - 39 & \overset{?}{=} & 0 \\ 9 + 48 - 18 - 39 & \overset{?}{=} & 0 \\ 57-57 & \overset{?}{=} & 0 \\ 0 & = & 0\ \checkmark \\ \hline \end{array} } \)

 

laugh

 Feb 22, 2018

13 Online Users

avatar
avatar